KEBEBASAN BERKONTRAK DALAM PANDANGAN HUKUM PROGRESIF - Achmad Busro (Faculty of Law, Universitas Diponegoro, 2011)
Freedom of contract is a principle that exists in the legal agreement, which gives freedom to the parties determine the content and the terms of the agreement with restrictions. The restrictions, which are not contrary to law, moral and public order. In this modern era, contracts tend to use a standard contract. Standard contract is a contract made by one party and another party only approve or not without any involvement in the making of the contract. Therefore, the principle of freedom of contract can not function properly in the implementation of standard contract. Given the aforementioned facts necessary to restore the principle of freedom of contract as appropriate for use by the public. One effort to overcome this is by using the principle of freedom of contract in the eyes of progressive law. View of progressive laws against the principle of freedom of contract has purpose to provide liberation and enlightenment in society. Progressive view of law is that law that frees where the scince of law has close relationship with the community. Is worth when it is said that the law is always tertanan in